ANALISIS FAKTOR YANG MEMPENGARUHI AGRESIVITAS PAJAK (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2012-2014) - Luke, Luke; Zulaikha, Zulaikha (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2016)
This study aims to examine empirically the effect of corporate social responsibility (CSR), return on asset (ROA), inventory intensity, and size of firm to tax aggressiveness. The population of this research was all manufacturing companies listed on the Indonesia Stock Exchange in the period 2012-2014. Sampling technique used was purposive sampling method. There were 190 companies that fulfilled the criteria of sampling. The result of this study showed that corporate social responsibility (CSR) and inventory intensity have negative significant influence to tax aggressivensess. Meanwhile, return on asset (ROA) and size of firm have positive significant relationship to tax aggressiveness.